The role of predictability and structure in word stress processing: an ERP study on Cairene Arabic and a cross-linguistic comparison - Domahs, Ulrike; Knaus, Johannes A.; El Shanawany, Heba; Wiese, Richard (Frontiers in Psychology, 2014)
This article presents neurolinguistic data on word stress perception in Cairene Arabic, in comparison to previous results on German and Turkish. The main goal is to investigate how central properties of stress systems such as predictability of stress and metrical structure are reflected in the prosodic processing of words. Cairene Arabic is a language with a regular foot-based word stress system, leading to highly predictable placement of word stress. An ERP study on Cairene Arabic is reported, in which a stress violation paradigm is used to investigate the factors predictability of stress and foot structure. The results of the experiment show that for Cairene Arabic the internal structure of prosodic words in terms of feet determines prosodic processing. This structure effect is complemented by a frequency effect for stress patterns.